Inventory Model Promoting Smart Production System with Zero Defects - Miriam, M. Renee; Martin, Nivetha; Anand, M. Clement Joe (International journal of applied and computational mathematics, 2023)
The production sectors are in the verge of augmenting the components of smart technology to evolve a hybrid production mechanism for quality sustenance with nil defective products. A quality production system producing products with no defects is termed a zero-defective production system. As every firm is striving to achieve the status of zero defectiveness an inventory model is developed in this article to handle all the defective items generated in a production lot using smart technology. In this model, the defective items are identified and classified into batches based on four levels of defectiveness. Level 1 compromises products that are less than 25% defective. Level 2 consists of the remaining products, up to 50% defective. Level 3 and Level 4 consist of products that are up to 75% and 100% defective. The main objective of this model is to maximize the net revenue by minimizing the repairing costs of the defective products after rightly subjecting them to any of the four levels using smart screening technology. The proposed model is highly beneficial to the production sectors producing varied products especially at a larger scale. The classification of the defective products using smart technology yields high net revenue with reduced costs associated with repairs and returns in comparison with the primary model based on Dutta. The validation of the proposed model and the sensitive analysis presents a clear picture of the dependency of net revenue maximization with the model parameters. The proposed profit maximization model may get deviated from the objective of zero-defects’ if any incongruences exist with the technology used in optimal classification of the effective products and this is identified as the limitation of the model.